Solid-State Hydrogen Storage Systems and the Relevance of a Gender Perspective - Erika Michela Dematteis; Jussara Barale; Marta Corno; Alessandro Sciullo; Marcello Baricco; Paola Rizzi (Energies, 2021)
This paper aims at addressing the exploitation of solid-state carriers for hydrogen storage, with attention paid both to the technical aspects, through a wide review of the available integrated systems, and to the social aspects, through a preliminary overview of the connected impacts from a gender perspective. As for the technical perspective, carriers to be used for solid-state hydrogen storage for various applications can be classified into two classes: metal and complex hydrides. Related crystal structures and corresponding hydrogen sorption properties are reviewed and discussed. Fundamentals of thermodynamics of hydrogen sorption evidence the key role of the enthalpy of reaction, which determines the operating conditions (i.e., temperatures and pressures). In addition, it rules the heat to be removed from the tank during hydrogen absorption and to be delivered to the tank during hydrogen desorption. Suitable values for the enthalpy of hydrogen sorption reaction for operating conditions close to ambient (i.e., room temperature and 1–10 bar of hydrogen) are close to 30 kJ·molH2−1. The kinetics of the hydrogen sorption reaction is strongly related to the microstructure and to the morphology (i.e., loose powder or pellets) of the carriers. Usually, the kinetics of the hydrogen sorption reaction is rather fast, and the thermal management of the tank is the rate-determining step of the processes. As for the social perspective, the paper arguments that, as it occurs with the exploitation of other renewable innovative technologies, a wide consideration of the social factors connected to these processes is needed to reach a twofold objective: To assess the extent to which a specific innovation might produce positive or negative impacts in the recipient socioeconomic system and, from a sociotechnical perspective, to explore the potential role of the social components and dynamics in fostering the diffusion of the innovation itself. Within the social domain, attention has been paid to address the underexplored relationship between the gender perspective and the enhancement of hydrogen-related energy storage systems. This relationship is taken into account both in terms of the role of women in triggering the exploitation of hydrogen-based storage playing as experimenter and promoter, and in terms of the intertwined impact of this innovation in their current conditions, at work, and in daily life.